2011
DOI: 10.1002/ptr.3678
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of Flavonoids: Influence of the Sequential Methoxylation State of the Flavonoid Structure

Abstract: Dracocephalum kotschyi Boiss. has been used as part of an ethnobotanical remedy against many forms of human cancer in Iran. It has been demonstrated that a flavonoid named xanthomicrol from D. kotschyi contributes to its preferential antiproliferative activity against malignant cells. In the present study, the antiproliferative activity of its flavonoid fraction was further characterized. Using liquid-liquid extraction and a semi-preparative reversed-phase HPLC method, eight flavonoid aglycones were isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 26 publications
4
89
2
Order By: Relevance
“…Recent pharmacological studies have confirmed presence of several methoxylated flavonoids with anti-cancer properties (Jahaniani et al 2005;Moghaddam et al 2012) and inhibitory effects on the lectin-induced cellular immune response in this plant (Faham et al 2008). Its leaf extract has been reported to have antihyperlipidemic (Ebrahim Sajjadi et al 1998), immunomodulatory (Amirghofran et al 2000), antinociceptive (Golshani et al 2004) and cytotoxic (Jahaniani et al 2005) effects.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent pharmacological studies have confirmed presence of several methoxylated flavonoids with anti-cancer properties (Jahaniani et al 2005;Moghaddam et al 2012) and inhibitory effects on the lectin-induced cellular immune response in this plant (Faham et al 2008). Its leaf extract has been reported to have antihyperlipidemic (Ebrahim Sajjadi et al 1998), immunomodulatory (Amirghofran et al 2000), antinociceptive (Golshani et al 2004) and cytotoxic (Jahaniani et al 2005) effects.…”
Section: Introductionmentioning
confidence: 88%
“…This diversity of structural patterns has made flavonoids a rich source of compounds with potential anticancer properties. Recent pharmacological studies suggested some methoxylated flavonoids (Xanthomicrol and Calycopterin) of D. kotschyi with anti-cancer properties (Jahaniani et al 2005;Moghaddam et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The extract was filtered and dried. Then 0.5 g dried extract was reconstituted in 2 mL DMSO for our mitochondrial experiments [13]. For standardization process the amounts of the eight flavonoids were measured in this extract.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, nepitrin (15) and homoplantagenin (16), which are flavone glucosides, were found to have noticeable AhR activity. (14) [17], and nepitrin (15) has been reported to have anti-inflammatory and gastroprotective activity [18,19]. Recently, several studies have reported that activation of AhR may be involved in various immune responses as described above; therefore, natural AhR ligands are expected to have beneficial regulatory roles in humans, mediating anti-allergy and anti-cancer effects.…”
Section: Identification and Ahr Activity Of Constituentsmentioning
confidence: 99%